Toward an Aesthetics of Science Fiction Television. - Siegel, Mark (Extrapolation (Kent State University Press))
Focuses on science fiction television programs. Acceptance of science fiction among television audiences; Aesthetic qualities of television science fiction; Social science models for television analysis; Limitations of television science fiction.